2020
DOI: 10.29408/veles.v4i2.2417
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Technological Pedagogical Content Knowledge (TPACK) on Practical EFL Teachers in Writing Context

Abstract: With the world demand to provide digital school, this study examines how the integration among technology, pedagogy and content knowledge in writing context as the part of TPACK framework on the practical EFL teachers. The samples of this study are 27 of practical English teachers divided into three level of achiever (low, middle, and high). They were taking the Writing and Assessment courses as the part of their education to achieve the bachelor degree in Universitas Hamzanwadi, a private University in Lombok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…Yet, the result on this study will not be eternal and final since it is assumed that the new transformation of online learning will be come a new culture several years later then teachers in Indonesia accustomed with it (Wijaya et al, 2021). On the other hand, although, finally from this study we know that EFL Indonesian willingness level in TPACK in middle, same like their level in TPACK itself, it is impossible to say that all instructors with varying levels of experience have the same level of willingness to comprehend and execute their TPACK (Ammade et al, 2020;Cahyono et al, 2016;Surayya & Asrobi, 2020). Thus, the result of the questionnaire used in this study may be different if it is applied in the other language area where technology become an alter ago, like IT teachers, or even economic, law, science, or health area.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Yet, the result on this study will not be eternal and final since it is assumed that the new transformation of online learning will be come a new culture several years later then teachers in Indonesia accustomed with it (Wijaya et al, 2021). On the other hand, although, finally from this study we know that EFL Indonesian willingness level in TPACK in middle, same like their level in TPACK itself, it is impossible to say that all instructors with varying levels of experience have the same level of willingness to comprehend and execute their TPACK (Ammade et al, 2020;Cahyono et al, 2016;Surayya & Asrobi, 2020). Thus, the result of the questionnaire used in this study may be different if it is applied in the other language area where technology become an alter ago, like IT teachers, or even economic, law, science, or health area.…”
Section: Discussionmentioning
confidence: 70%
“…To be more specific, teachers' TPACK on writing are in moderate level. If teachers' TPACK is examined in a broad sense, it suggests they have a decent degree of TPACK, but it is difficult for them to adapt their specialized content knowledge to specific technology (Ammade et al, 2020;Surayya & Asrobi, 2020). The findings revealed that Education Technology graduates possessed a strong grasp of subject and pedagogical competence (Utama's, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also done several investigations on the implementation of TPACK [1], [6], [26]- [34]. In this case, Surayya and Asrobi [1] examine how integrating technology, pedagogy, and content knowledge in the writing context is part of the TPACK framework for practical EFL teachers.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…The outbreak of the new Coronavirus in the past two years has forced many walks of life to take on abrupt changes in the ways they operate. People were unprepared for this "unpredictable dangerous pandemic" and were forced to implement drastic measures to cope with the challenge [1]. The transition to online classes in the midst of pandemic surely causes challenges for educators [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation